2004
DOI: 10.1111/j.1474-9728.2004.00102.x
|View full text |Cite
|
Sign up to set email alerts
|

Innate immunity in aging: impact on macrophage function

Abstract: SummaryInnate and adaptive immune functions decline with age, leading to increased susceptibility to infectious diseases and cancer, and reduced responses to preventive vaccination in the elderly population. Macrophages function as 'pathogen sensors' and play an important role in the initiation of inflammatory responses, elimination of pathogens, manipulation of the adaptive immune response and reparation of damaged tissue. In this paper, we review the literature addressing the impact of aging on the macrophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
236
1
14

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 375 publications
(263 citation statements)
references
References 69 publications
6
236
1
14
Order By: Relevance
“…There are many circumstances in which the host's immunological environment is altered. These may include various forms of inherent immunodeficiencies; altered immune status due to aging [7][8][9][10][11][12][13][14], as well as results of prior and/or concurrent infections [15][16][17][18][19][20][21][22]. Previously, we have shown that a number of adjuvant formulations differ in their ability to potentiate the immunogenicity of a malaria vaccine under the altered immunological environment created by Interferon-γ and Interleukin-4 knockouts [23].…”
Section: Introductionmentioning
confidence: 99%
“…There are many circumstances in which the host's immunological environment is altered. These may include various forms of inherent immunodeficiencies; altered immune status due to aging [7][8][9][10][11][12][13][14], as well as results of prior and/or concurrent infections [15][16][17][18][19][20][21][22]. Previously, we have shown that a number of adjuvant formulations differ in their ability to potentiate the immunogenicity of a malaria vaccine under the altered immunological environment created by Interferon-γ and Interleukin-4 knockouts [23].…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, Walford hypothesized that increased immune genetic diversity and dysfunction of immune system cause aging-related pathophysiological processes with the growth of the age, termedMacrophage, a bridge linking innate and adaptive immune system, shows the dysregulation of chemokine and cytokine secretion, which may result in poor responses to infection and protracted repair processes with aging (Plowden et al 2004). Several experimental evidences have demonstrated that LPS-activated macrophages from aged mice and humans produced more prostaglandin E2 (PGE2) than those from younger individuals Wu et al 1998).…”
mentioning
confidence: 99%
“…The elderly are more susceptible to peripheral infections with increased incidence of disability and mortality rates for individuals 65 years of age and older (Plackett et al, 2004;Plowden et al, 2004). Aging is related to a proinflammatory environment characterized by constitutively elevated levels of several NF-jB-driven proinflammatory cytokines, such as IL-6, IL-1b, and TNFa, in the absence of overt disease conditions, the so-called inflamm-aging (Franceschi et al, 2000).…”
Section: Introductionmentioning
confidence: 99%